Analisis Pengaruh Keterlibatan Keluarga terhadap Kinerja Perusahaan di Indonesia - Santi Yopie; Chrislin Chrislin (Politeknik Ganesha Medan, 2022)
Family businesses have steadily dominated the economy sector in recent decades. A number of scholars have focused on the link between management by family members and firm performance. However, the findings are not conclusive and vary. As a result, a re-examination is necessary. The goal of this research is to determine the possible influences caused by family presence, non-family shareholders, professional president directors, and founder-managed firms on firm performance, as well as the link between family presence and firm performance when family firm reputation is taken into the account. Firm performance was valued by measuring return on asset and equity, sales growth, and tobin’s q. This study examined 600 samples consisting 120 family firms in manufacturing and service sectors on Indonesia’s Stock Exchange beginning with the year 2016 – 2020. To make data analysis more straightforward, panel regression research (time series and cross-sectional data) was conducted utilizing PLS 3.0 software. The study results prove family presence, professional president directors, and founder-managed firms have positive impact on firm performance. Meanwhile, non-family shareholders showed negative impact towards firm performance. Furthermore, the findings of this study also show the favorable impact of family presence on firm performance may be bolstered by family firm reputation.